The Batman vs. Dracula [videorecording (DVD)] - Kane, Bob (Batman., 2005)
Gotham City is terrorized not only by recent escapees Joker and Penguin, but by the original creature of the night, Dracula! Can Batman stop the ruthless vampire before he turns everyone in the city, including The Caped Crusader, into his mindless minions.